2019
DOI: 10.3390/sports7010028
|View full text |Cite
|
Sign up to set email alerts
|

Inertial Sensors for Performance Analysis in Combat Sports: A Systematic Review

Abstract: The integration of technology into training and competition sport settings is becoming more commonplace. Inertial sensors are one technology being used for performance monitoring. Within combat sports, there is an emerging trend to use this type of technology; however, the use and selection of this technology for combat sports has not been reviewed. To address this gap, a systematic literature review for combat sport athlete performance analysis was conducted. A total of 36 records were included for review, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 40 publications
0
50
1
Order By: Relevance
“…Of these seventeen, four (4/17-23.5%) only used an accelerometer and gyroscope and the remaining 13 (13/17-76.5%) also incorporated a magnetometer. The highest reported accelerometer range was ±16 g and the lowest was ±2 g. Compared to our laboratories, previous systematic literature review on the use of inertial sensors in combat sport [3], which reported a maximum and minimum operating range of ±750 g and ±8 g, respectively, these ranges are low. Nonetheless, rowing is a sport that does not typically consist of high impact situations and thus ±16 g and even ±2 g should have a minute risk of sensor saturation.…”
Section: Algorithmscontrasting
confidence: 66%
See 4 more Smart Citations
“…Of these seventeen, four (4/17-23.5%) only used an accelerometer and gyroscope and the remaining 13 (13/17-76.5%) also incorporated a magnetometer. The highest reported accelerometer range was ±16 g and the lowest was ±2 g. Compared to our laboratories, previous systematic literature review on the use of inertial sensors in combat sport [3], which reported a maximum and minimum operating range of ±750 g and ±8 g, respectively, these ranges are low. Nonetheless, rowing is a sport that does not typically consist of high impact situations and thus ±16 g and even ±2 g should have a minute risk of sensor saturation.…”
Section: Algorithmscontrasting
confidence: 66%
“…In sport and biomechanics research, the golden standard is commonly a multi-camera retro-reflective motion capture system that can track human positions in three-dimensional space. From this data, the acceleration and rotation of the body part can be calculated and compared to inertial sensor data [3]. The competitive setting for rowing is on-water and thus retro-reflective motion capture is not a viable option.…”
Section: Study Design and Hardwarementioning
confidence: 99%
See 3 more Smart Citations